ASSESSING CLINICAL OUTCOMES OF SGLT2 INHIBITOR THERAPY IN ELDERLY HFrEF PATIENTS WITH AND WITHOUT DIABETES: A SINGLE-CENTRE STUDY - I, Hazwani; Chuan, Ng Ooi; Bidin, Mohammad Zulkarnain bin; RMR, Raja Abdul Wafy (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Heart failure with reduced ejection fraction (HFrEF) is a complex syndrome resulting in decreased ventricular function, leading to symptomatic left ventricle dysfunction and global cardiovascular morbidity and mortality. Type 2 Diabetes Mellitus (T2DM) escalates cardiovascular risk, necessitating tight glucose control. Sodium-glucose cotransporter 2 inhibitors (SGLT2i) promise to improve cardiovascular outcomes and diabetes therapy. METHODOLOGY This study aimed to assess the efficacy and safety profile of SGLT2i in elderly HFrEF patients, both with and without T2DM. In this retrospective observational study, we examined patients on SGLT2i aged 65 and older with an ejection fraction (EF) of ≤40% from our cardiology clinic. Patient medical records from 2018–2023 provided data for analysis, including demographics, comorbidities, changes in EF, New York Heart Association (NYHA) shifts, estimated glomerular filtration rate (eGFR) reduction, hospitalisation and mortality among patients with and without T2DM. RESULTS From 934 SGLT2 inhibitor-treated patients, our study focused on 167 elderly HFrEF patients, divided into T2DM (125 patients) and non-T2DM (42 patients). Both groups had similar demographics. Significantly, 80.6% of T2DM patients had hypertension, compared to 37.2% of nonT2DM patients (P <0.001). Both groups had improved EF (54% vs. 51.2%, P = 0.859). Guideline-Directed Medical Therapy (GDMT) showed a moderate association with observed outcomes, with no significant differences in EF or NYHA improvement between T2DM and non-T2DM patients (P = 0.859, P = 0.137, respectively). In T2DM patients, cardiovascular events, total hospitalisation, and mortality were greater but not statistically significant (P = 0.38, P = 0.128, and P = 0.113, respectively). Notably, patients without T2DM exhibited a more pronounced reduction in eGFR (P = 0.018). CONCLUSION SGLT2 inhibitors improved EF and NYHA classification in elderly patients with HFrEF, regardless of T2DM status. On the other hand, the presence of both T2DM and chronic kidney disease (CKD) emerged as significant risk factors associated with higher rates of hospitalisation and mortality.